Catalyst with precious metals supported on grain boundaries and surfaces, its manufacturing method and uses
By introducing precious metals and cerium-zirconium composite oxides distributed at the grain interface and surface into the catalyst, the stability and activity of the catalyst at high temperature are solved, and the long-term effectiveness of the catalyst at high temperature and the saving of precious metals are achieved.
Patent Information
- Application Number
- JP2024542098
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-14
- Filing Date
- 2023-02-13
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2043-02-13
AI Technical Summary
The precious metal catalysts in existing automotive exhaust catalytic converters are prone to elemental diffusion, particle aggregation and growth in high temperature environments, resulting in a reduction in catalytic activity and making it difficult to maintain high temperature stability and long-term use efficiency.
By introducing precious metals and/or cerium-zirconium composite oxides distributed at the grain interface and surface into the catalyst, a catalyst formulation and manufacturing process with specific chemical composition is adopted to control the distribution and state of precious metals, avoid particle movement and aggregation at high temperatures, and improve the high temperature stability and activity of the catalyst.
It effectively improves the high temperature resistance of the catalyst, maintains catalytic activity, reduces the amount of precious metals, and extends the service life.
Smart Images

Figure 2025502970000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application is filed based on a Chinese patent application with application number 202210135425.8 and filing date of February 14, 2022, and claims priority to the Chinese patent application, the entire contents of which are hereby incorporated by reference into this application.
[0002] The present invention relates to the technical field of precious metal catalysts, and in particular to catalysts having precious metals supported on grain boundaries and surfaces, and to a method for producing the same and uses thereof. [Background technology]
[0003] According to research, with the increase in the number of automobiles owned in the world every year, automobile exhaust pollution has become the main source of urban air pollution, and the environmental problems caused by automobile exhaust emissions are becoming more and more serious. Automobile exhaust catalytic converters are an effective solution for purifying automobile exhaust gas, and their core is a three-way catalyst carrying precious metals. Usually, automobile exhaust three-way catalysts are composed of a honeycomb carrier, precious metals, active coating, etc., and their service life is mainly determined by the active coating material and manufacturing process of the three-way catalyst, where the active coating material includes cerium zirconium composite oxide and alumina, etc., and the precious metal is supported on the active coating. In practical applications, the environment in which automobile exhaust three-way catalysts are placed is poor, not only contains water vapor, but also has high temperatures, sometimes reaching 900°C or more, so the catalyst, coating material, precious metal, etc. require high-temperature stability performance. Therefore, in order to ensure the conversion efficiency of automobile exhaust gas catalysts and maintain the catalytic activity of cerium-zirconium composite oxide-supported precious metal catalysts, it is necessary to prevent high-temperature aging of the coating material containing the cerium-zirconium-supported precious metal in a high-temperature environment as much as possible, while preventing high-temperature sintering of the cerium-zirconium as much as possible, and preventing the precious metal particles from migrating, agglomerating, growing, or being wrapped in a coating material such as cerium-zirconium or alumina at high temperatures, which would reduce or lose the catalytic activity. In oxidation-type catalysts such as natural gas catalytic combustion and organic exhaust gas treatment, precious metal catalysts are also required to have high high-temperature stability. Summary of the Invention [Problem to be solved by the invention]
[0004] Based on the above-mentioned situation of the prior art, the object of the present invention is to provide a catalyst carrying a precious metal on grain boundaries and surfaces, and its manufacturing method and use, which is used to prevent or delay element diffusion between crystal grains and on the surface by dispersing a precious metal on the grain boundaries and surfaces of alumina and / or cerium-zirconium composite oxide, and to suppress the migration, aggregation and growth of precious metal particles at high temperatures, thereby producing a cerium-zirconium-based precious metal catalyst that is more resistant and stable to high temperatures; and the catalyst carrying a precious metal on the grain boundaries and surfaces of alumina and / or cerium-zirconium composite oxide produced as above is used to produce a honeycomb-type precious metal catalyst slurry, and the slurry is applied to a honeycomb to produce a honeycomb-type precious metal catalyst, thereby effectively improving the high temperature resistance and stability of the honeycomb-type precious metal catalyst, maintaining the catalytic activity under long-term high temperature use conditions of the catalyst, and reducing the amount of precious metal used. [Means for solving the problem]
[0005] In order to achieve the above object, according to a first aspect of the present invention, there is provided a catalyst having a precious metal supported on grain boundaries and surfaces, the catalyst comprising a precious metal G, alumina and / or a cerium-zirconium composite oxide, the precious metal G being dispersed on grain boundaries and surfaces of the alumina and / or cerium-zirconium composite oxide, and the general chemical formula of the cerium-zirconium composite oxide is: x Zr y M z O 2-α D δ where: M is the doping element of the cation, D is the doping element of the anion, 0≦x≦1, 0≦y≦1, 0≦z<0.5, and x, y, and z satisfy x+y+z=1; 0≦α≦0.1 and 0≦δ≦0.1.
[0006] According to a second aspect of the present invention, there is provided a honeycomb-type precious metal catalyst, the catalyst comprising a honeycomb carrier, a precious metal G and an active coating, the active coating being alumina and / or a cerium-zirconium composite oxide Ce. x Zr y Mz O 2-α D δ The precious metal G is dispersed on the grain boundaries and surfaces of the alumina and / or cerium-zirconium composite oxide, M is the doping element of the cation, D is the doping element of the anion, 0≦x≦1, 0≦y≦1, 0≦z<0.5, and x, y, and z satisfy x+y+z=1; 0≦α≦0.1 and 0≦δ≦0.1.
[0007] Furthermore, the percentage of the cerium-zirconium composite oxide to the total mass of the active coating is 0 to 100%, preferably 30 to 70%.
[0008] Furthermore, the precious metal G at the grain boundaries and surface is in the metallic state, or in the metallic and oxidized states.
[0009] Furthermore, the precious metal G includes one or a combination of one or more of Pt, Pd, Rh, Ir, Os, Ru, Au, and Ag, and is preferably one or a combination of one or more of Pt, Pd, Rh, and Ru.
[0010] Furthermore, the doping element M is one or a combination of one or more of rare earth elements other than cerium, transition metal elements other than zirconium and rare earth elements, alkaline earth metal elements, Al, Si, Ga, Sn, and Bi, and the rare earth elements other than cerium include La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and Y, and preferably La, Pr, Nd, Sm, Eu, Gd, Tm, Yb, Y, the transition metal elements include Sc, Ti, V, Mn, Fe, Co, Ni, Cu, Zn, Nb, Mo, Hf, Ta, W, preferably Ti, Mn, Fe, Co, Ni, Cu, Nb, Hf, W, Mo, the alkaline earth metal elements include Be, Mg, Ca, Sr, Ba, preferably Mg, Sr, Ba, and said doping element D comprises one or a combination of more than one of the anions N, F and P.
[0011] Furthermore, the cerium-zirconium composite oxide in the catalyst has a core-shell structure, the core contains a rare earth element and zirconium, and the content of yttria in the shell is higher than the total content of yttria in the composite oxide. The present invention designs the element types and contents of the shell and / or core based on the theoretically calculated difference between the element surface energy and the oxygen vacancy formation energy, thereby comprehensively improving the thermal stability and oxygen storage / release performance of the cerium-zirconium composite oxide.
[0012] Furthermore, the cerium-zirconium composite oxide in the catalyst includes a cerium-zirconium oxide with an element gradient distribution structure. The present invention designs the element types and contents in the gradient structure based on the theoretically calculated difference between the element surface energy and the oxygen vacancy formation energy, and gradually increases or decreases the content of a specific element from the inside to the outside in the radial direction of the crystal grain, thereby comprehensively improving the thermal stability and oxygen storage and release performance of the cerium-zirconium composite oxide.
[0013] Furthermore, the material of the honeycomb carrier is a porous ceramic or a metal.
[0014] Furthermore, the amount of the precious metal G supported in the catalyst is 0.01% to 3%, preferably 0.1% to 2%, in terms of mass fraction.
[0015] Furthermore, the amount of the precious metal G supported in the catalyst is 0.01 to 2.8 g / L, and preferably 0.1 to 2 g / L.
[0016] According to a third aspect of the present invention, there is provided a method for producing a catalyst having a noble metal supported on the grain boundaries and surface as described in the first aspect of the present invention, A step S1 of uniformly mixing a cerium-zirconium composite oxide and / or activated alumina with a liquid salt of a precious metal G; Step S2, which performs one or two heat treatments on the product obtained in step S1; and Step S3, in which the product obtained in Step S2 is reduced and roasted once or twice in air or a reducing atmosphere to obtain a catalyst in which a precious metal is supported on the grain boundaries and surfaces of a cerium-zirconium composite oxide and / or activated alumina.
[0017] According to a fourth aspect of the present invention, there is provided a method for producing the honeycomb-type precious metal catalyst according to the second aspect of the present invention, comprising coating the honeycomb-type precious metal catalyst with one or more coating materials in layers or regions, the coating materials being selected from the group consisting of cerium-zirconium composite oxide, alumina, cerium-zirconium composite oxide carrying a precious metal on its grain boundaries and surfaces, alumina carrying a precious metal on its grain boundaries and surfaces, and a mixture of cerium-zirconium composite oxide and alumina carrying a precious metal on its grain boundaries and surfaces, and the production of the honeycomb-type precious metal catalyst includes the steps of: Step B1, in which the coating material is mixed uniformly with an adhesive, an acidity regulator and water in one or more steps to prepare a coating slurry; Step B2 of applying the coating slurry obtained in step B1 to a honeycomb carrier in one or more steps, or applying the coating slurry to the honeycomb carrier in regions or layers, and drying the honeycomb carrier; and Step B3, in which the product obtained in Step B2 is heat-treated and / or roasted in air or a reducing atmosphere to obtain a precious metal honeycomb catalyst.
[0018] According to a fifth aspect of the present invention, there is provided a method for producing a honeycomb-type precious metal catalyst described in the second aspect of the present invention, in which a cerium-zirconium composite oxide and / or alumina, a liquid salt of a precious metal, an adhesive, an acidity regulator and water are uniformly mixed in one or more steps to produce a coating slurry, the resulting product is applied to a honeycomb carrier in one or more steps, or applied to a honeycomb carrier by region or layer, and then dried, and the dried honeycomb carrier is heat-treated or / and reduced-roasted in a reducing atmosphere to obtain a honeycomb-type precious metal catalyst.
[0019] Furthermore, the heat treatment temperature is 200 to 800° C. and the heat treatment time is 0.5 to 24 hours, preferably the heat treatment temperature is 400 to 700° C. and the heat treatment time is preferably 1 to 12 hours.
[0020] Furthermore, the roasting temperature is 400 to 700° C. and the roasting time is 0.5 h to 24 h, preferably the roasting temperature is 450 to 600° C. and the roasting time is preferably 1 h to 12 h.
[0021] Furthermore, the reducing atmosphere includes one or more of CO and H2.
[0022] Furthermore, the liquid salt of the precious metal G includes one or a combination of one or more of the following: a molten salt or an aqueous solution of a chloride, a nitrate, and an acetate.
[0023] According to a sixth aspect of the present invention, there is provided the use of the catalyst according to the first and second aspects of the present invention in the fields of automobile exhaust gas purification, industrial organic exhaust gas treatment, natural gas catalytic combustion, petrochemistry, hydrogen energy and batteries. Effect of the Invention
[0024] As described above, the present invention provides a catalyst with a precious metal supported on the grain boundaries and surface, a honeycomb-type precious metal catalyst, and its manufacturing method and use. The catalyst with a precious metal supported on the grain boundaries and surface and the honeycomb-type precious metal catalyst provided by the present invention disperse the precious metal G on the grain boundaries and surface of alumina and / or cerium-zirconium composite oxide, thereby improving the anchoring effect of the precious metal and preventing the migration, aggregation and growth of precious metal particles, maintaining the catalytic activity and high-temperature stability of the precious metal catalyst, and reducing the amount of precious metal used. [Brief description of the drawings]
[0025] [Figure 1] 1 is a flowchart of a method for producing a catalyst having a precious metal supported on the grain boundaries and the surface according to an embodiment of the present invention. [Diagram 2] 2 is a flowchart showing a method for manufacturing a honeycomb-type precious metal catalyst according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] In order to make the objectives, technical solutions and advantages of the present invention clearer, the present invention will be described in more detail below in conjunction with specific embodiments and with reference to the accompanying drawings. It should be understood that these descriptions are merely illustrative and do not limit the scope of the present invention. Furthermore, in the following description, descriptions of known structures and techniques are omitted to avoid unnecessary confusion of the concept of the present invention.
[0027] An embodiment of the present invention provides a catalyst with a precious metal supported on the grain boundary and surface, the catalyst having a precious metal G dispersed on the grain boundary and surface of alumina and / or cerium zirconium composite oxide, the general chemical formula of which is Ce x Zr y M z O 2-α D δ M is a doping element of the cation, D is a doping element of the anion, and the value range of each element is as follows: 0≦x≦1, 0≦y≦1, 0≦z≦0.5, and x, y, and z satisfy x+y+z=1; 0≦α≦0.1 and 0≦δ≦0.1.
[0028] An embodiment of the present invention further provides a honeycomb-type precious metal catalyst, the catalyst comprising a honeycomb carrier, a precious metal G and an active coating, the active coating being alumina and / or a cerium-zirconium composite oxide Ce. x Zr y M z O 2-α D δ The precious metal G is alumina and / or cerium zirconium composite oxide Ce x Zr y M z O 2-α D δ The noble metal G is in a metallic state, or in a metallic and oxidized state, preferably in a metallic state, and the noble metal G is alumina and / or a cerium-zirconium composite oxide Ce. x Zr y M z O 2-α Dδ The precious metal G is dispersed in the grain boundaries and on the surface of the active coating and is in a metallic state, which is more advantageous for the catalytic effect. The precious metal G may be one or a combination of one or more of Pt, Pd, Rh, Ir, Os, Ru, Au and Ag, and preferably, the precious metal G is one or a combination of one or more of Pt, Pd, Rh and Ru. The amount of the precious metal G supported in the catalyst is 0.01-3%, preferably 0.1-2%, in mass fraction.
[0029] The doping element M of the cerium-zirconium composite oxide of the present invention is one or a combination of one or more of rare earth elements other than cerium, transition metal elements other than zirconium and rare earth elements, alkaline earth metal elements, Al, Si, Ga, Sn, and Bi. The rare earth elements other than cerium include La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and Y, and preferably La, Pr, Nd, Sm, Eu, Gd, The doping element D may be one or a combination of more than one of the anions N, F, P. The transition metal elements include Sc, Ti, V, Mn, Fe, Co, Ni, Cu, Zn, Nb, Mo, Hf, Ta, W, and preferably Ti, Mn, Fe, Co, Ni, Cu, Nb, Hf, W, Mo. The alkaline earth metal elements include Be, Mg, Ca, Sr, Ba, and preferably Mg, Sr, Ba. The doping element D may be one or a combination of more than one of the anions N, F, P.
[0030] The cerium zirconium composite oxide in the catalyst provided in the embodiment of the present invention comprises a core-shell structure. For other features and advantages of the core-shell structure of the cerium zirconium composite oxide, please refer to the Chinese patent application with application number CN202010982980.5, filed on September 17, 2020, and the invention title "Cerium zirconium composite oxide with core-shell structure and its manufacturing method" and its full content description. The present invention designs the element types and contents of the shell and / or core based on the theoretically calculated difference between the element surface energy and the oxygen vacancy formation energy, and comprehensively improves the thermal stability and oxygen storage and release performance of the cerium zirconium composite oxide.
[0031] The cerium zirconium composite oxide in the catalyst provided in the embodiment of the present invention includes a cerium zirconium composite oxide with an element gradient distribution structure. For other features and advantages of the element gradient distribution structure of the cerium zirconium composite oxide, please refer to the Chinese patent application with application number CN202010982979.2, named "Cerium zirconium composite oxide with element gradient distribution and its manufacturing method" filed on September 17, 2020, and its full content description. The present invention designs and controls the element types and contents in the gradient structure based on the theoretically calculated difference between the element surface energy and the oxygen vacancy formation energy, and gradually increases or decreases the content of a specific element from the inside to the outside in the radial direction of the crystal grain, thereby comprehensively improving the thermal stability and oxygen storage and release performance of the cerium zirconium composite oxide.
[0032] The present invention further provides a method for producing the catalyst having a precious metal supported on the grain boundaries and surface thereof. Fig. 1 shows a flow chart of the method for producing the catalyst having a precious metal supported on the grain boundaries and surface thereof according to the embodiment of the present invention, and includes steps S1 to S3.
[0033] In S1, alumina and / or cerium zirconium composite oxide Ce is mixed in a predetermined composition ratio. x Zr y M z O 2-α D δ and a liquid salt of a precious metal G, the liquid salt of the precious metal G including one or more combinations of a molten salt or solution of a chloride salt, a nitrate salt, and an acetate salt, and alumina and / or a cerium-zirconium composite oxide Ce in this step are mixed uniformly. x Zr y M z O 2-α D δ The mixing ratio of the precious metal G is 0.01 to 3%, preferably 0.1 to 2%, in terms of mass fraction, depending on the amount of the precious metal G supported.
[0034] In S2, the product obtained in step S1 is subjected to heat treatment once or twice, and the heat treatment temperature may be 200-800°C and the heat treatment time is 0.5h-24h, and preferably, the heat treatment temperature is 400-700°C and the heat treatment time is 1h-12h.
[0035] In step S3, the product obtained in step S2 is reduced and roasted once or twice in air or a reducing atmosphere to obtain alumina and / or cerium-zirconium composite oxide (Ce). x Zr y M z O 2-α D δ A catalyst having a precious metal dispersed on the grain boundary and surface of the catalyst is obtained, the roasting temperature may be 400-800°C, and the roasting time may be 0.5h-24h, preferably the roasting temperature is 450-600°C, and the roasting time is 1h-12h, the reducing atmosphere may contain one or a combination of CO and H2, and the reducing atmosphere may contain a small amount of O2, and the volume percentage content of O2 is 10% or less.
[0036] In the embodiment of the present invention, when performing the heat treatment in step S2, by controlling the appropriate temperature, the grain boundaries of the substrate start to be activated and become a path for the precious metal to diffuse, and by controlling the heat treatment time, the depth and distribution of the precious metal diffusing along the grain boundaries can be controlled. In step S3, by controlling the reducing atmosphere, the reduction temperature, and the reduction time, the precious metal at the grain boundaries and the surface can be reduced, or a part of it can be reduced. By distributing the precious metal at the grain boundaries and the surface of the cerium zirconium composite oxide in steps S2 and S3, on the one hand, it is used to prevent or delay element diffusion between crystal grains or on the surface of the cerium zirconium composite oxide, to prevent sintering aging and a decrease in the specific surface area of the cerium zirconium composite oxide, and to increase the thermal stability of the cerium zirconium composite oxide, and on the other hand, the anchoring action of the precious metal by the grain boundaries and the surface of the cerium zirconium composite oxide delays the movement, aggregation, and growth of the precious metal particles at high temperatures, and produces alumina and / or cerium zirconium composite oxide Ce that is more resistant and stable to high temperatures. x Zr yM z O 2-α D δ A catalyst is produced in which a precious metal is supported on the grain boundaries and surface of the catalyst.
[0037] The embodiment of the present invention further provides a method for manufacturing the above-mentioned honeycomb-type precious metal catalyst, and one or more coating materials are applied to the honeycomb-type precious metal catalyst in layers or regions, and the coating materials are cerium zirconium composite oxide, alumina, cerium zirconium composite oxide with precious metal supported on grain boundaries and surfaces, alumina with precious metal supported on grain boundaries and surfaces, and a mixture of cerium zirconium composite oxide and alumina with precious metal supported on grain boundaries and surfaces. FIG. 2 shows a flow chart of the method for manufacturing the honeycomb-type precious metal catalyst according to the embodiment of the present invention; Step B1, in which the coating material is mixed uniformly with an adhesive, an acidity regulator and water in one or more steps to prepare a coating slurry; Step B2 of applying the coating slurry obtained in step B1 to a honeycomb carrier in one or more steps, or applying the coating slurry to the honeycomb carrier in regions or layers, and drying the honeycomb carrier; and step B3 of heat-treating and / or roasting the product obtained in step B2 to obtain a precious metal honeycomb catalyst. The heat treatment temperature in this step may be 200-800°C, and the time is 0.5h-24h, preferably the heat treatment temperature is 400-700°C, and the heat treatment time is 1h-12h. The roasting temperature in this step may be 400-800°C, and the time is 0.5h-24h, preferably the roasting temperature is 450-600°C, and the roasting time is 1h-12h. The roasting atmosphere in this step may be air atmosphere roasting or reducing atmosphere roasting, and the reducing roasting atmosphere may be one or more of CO and H2.
[0038] The embodiment of the present invention further provides another method for manufacturing the above-mentioned honeycomb-type precious metal catalyst, which includes the following steps: Coating one or more of the catalysts carrying precious metal on the grain boundaries and surfaces of cerium-zirconium composite oxide, alumina, cerium-zirconium composite oxide and / or activated alumina on a honeycomb carrier in layers or regions; Through a heat treatment step and a roasting step, and controlling the atmosphere, temperature and time of the heat treatment and roasting, a honeycomb-type precious metal catalyst carrying precious metal G on the grain boundaries and surfaces of alumina and / or cerium-zirconium composite oxide is obtained; The anchoring effect of the precious metal on the grain boundaries and surfaces can prevent the migration and growth of precious metal particles, thereby maintaining the catalytic activity and high-temperature stability of the precious metal catalyst; Improving the thermal stability performance of the honeycomb-type precious metal catalyst under long-term high-temperature environmental conditions, ensuring the catalytic activity of the catalyst, and reducing the amount of precious metal used.
[0039] The embodiments of the present invention further provide applications of the above-mentioned catalysts with precious metals supported on the grain boundaries and surfaces and the above-mentioned honeycomb-type precious metal catalysts in the fields of automobile exhaust gas purification, industrial organic exhaust gas treatment, natural gas catalytic combustion, petrochemistry, hydrogen energy, and batteries. The catalysts with precious metals supported on the grain boundaries and surfaces and the honeycomb-type precious metal catalysts provided in the embodiments of the present invention have good high-temperature stability performance and can meet the application needs of various related fields.
[0040] The present invention will now be further described with reference to specific examples.
[0041] Comparative Example 1 A fixed volume of palladium nitrate and platinum nitrate solution with a loading of 0.9% palladium and 0.3% platinum was weighed out to 200gCe 0.52 Zr 0.36 La 0.05 Y 0.07 The cerium-zirconium supported precious metal catalyst sample was obtained by uniformly mixing with O2 powder, drying the sample at 110°C for 4 hours, and then roasting the dried sample at 500°C for 5 hours in air atmosphere. An appropriate amount of the cerium zirconium composite oxide-supported precious metal catalyst sample prepared as above was aged at 1000°C for 4 hours. Then, the cerium zirconium composite oxide-supported precious metal catalyst powder was tableted, crushed, and sieved to obtain a granular cerium zirconium composite oxide-supported precious metal catalyst of 30-40 mesh, and then the catalytic performance test was performed on the granular catalyst. The catalytic test adopted a simulated automobile exhaust gas mixture, and the contents (volume ratios) of each component were CO content 1.5%, NO content 900ppm, HC content 900ppm, O2 content 1.2%, CO2 content 12%, and the balance N2, and the space velocity was 50000 / h. The ignition temperature (T50) of the sample for the catalytic conversion of CO, NO, and HC was tested, and the results were that the ignition temperature of CO was 325°C, the ignition temperature of NO was 339°C, and the ignition temperature of HC was 318°C.
[0042] Comparative Example 2 200g Ce 0.52 Zr 0.36 La 0.05 Y 0.07 O2 powder, 200g of activated alumina and an appropriate amount of deionized water were made into a slurry, and palladium nitrate and platinum nitrate were added in amounts of 0.45% palladium and 0.15% platinum based on the total mass of the honeycomb carrier active coating, and mixed uniformly. An adhesive, an acidity regulator, etc. were then added to make a coating slurry. The slurry was applied to a ceramic honeycomb carrier in an amount of 1.2g / L in total loading of the honeycomb catalyst precious metals. The coated honeycomb carrier was then dried at 110°C for 4 hours, and finally the honeycomb carrier was roasted in an air atmosphere at 500°C for 5 hours to obtain a honeycomb-type precious metal catalyst. The honeycomb-type precious metal catalyst prepared as above was aged at 1000°C for 4 hours, and then cut into honeycomb-type precious metal catalyst samples with a diameter of 0.5-1 cm. Then, the cut honeycomb-type precious metal catalyst samples were subjected to catalytic performance tests. The catalytic test adopted a simulated automobile exhaust gas mixture, and the contents (volume ratios) of each component were CO content 1.5%, NO content 900 ppm, HC content 900 ppm, O2 content 1.2%, CO2 content 12%, and the balance N2. The space velocity was 50000 / h. The ignition temperature (T50) of the sample for catalytic conversion of CO, NO, and HC was tested, and the results were that the ignition temperature of CO was 314°C, the ignition temperature of NO was 329°C, and the ignition temperature of HC was 311°C.
[0043] Comparative Example 3 A certain volume of palladium nitrate and rhodium nitrate solution with a loading of 1.2% palladium and 0.2% rhodium was weighed and added to 200g of Ce. 0.16 Zr 0.78 La 0.02 Nd 0.04 The cerium-zirconium supported precious metal catalyst sample was obtained by uniformly mixing with O2 powder, drying the sample at 110°C for 4 hours, and roasting the dried sample at 500°C for 5 hours in an air atmosphere to obtain a cerium-zirconium supported precious metal catalyst sample. The catalyst performance test was carried out on the sample, and the sample preparation steps and catalyst test conditions were the same as those in Comparative Example 1. The test results showed that the ignition temperature of CO was 330°C, the ignition temperature of NO was 323°C, and the ignition temperature of HC was 331°C.
[0044] Comparative Example 4 200g Ce 0.16 Zr 0.78 La 0.02 Nd 0.04O2 powder, 200g of activated alumina and an appropriate amount of deionized water were mixed together to form a slurry, and palladium nitrate and rhodium nitrate were added to the total mass of the honeycomb carrier active coating in an amount of 0.6% palladium and 0.1% rhodium, and mixed uniformly. An adhesive, an acidity regulator, etc. were added to form a coating slurry, and the slurry was coated on a ceramic honeycomb carrier in an amount of 1.4g / L of total honeycomb catalyst precious metals. The coated honeycomb carrier was dried at 110°C for 4 hours, and finally the honeycomb carrier was roasted in an air atmosphere at 500°C for 5 hours to obtain a honeycomb-type precious metal catalyst. The sample was subjected to a catalytic performance test, and the sample preparation steps and catalytic test conditions were the same as those of Comparative Example 2. The test results showed that the ignition temperature of CO was 326°C, the ignition temperature of NO was 319°C, and the ignition temperature of HC was 327°C.
[0045] Example 1 A fixed volume of palladium nitrate and platinum nitrate solution with a loading of 0.9% palladium and 0.3% platinum was weighed out to 200gCe 0.52 Zr 0.36 La 0.05 Y 0.07 The sample was uniformly mixed with O2 powder, dried at 110°C for 4 hours, heat-treated at 550°C for 4 hours, and finally roasted at 500°C for 5 hours in a hydrogen atmosphere to obtain the catalyst sample PdPt / Ce with precious metals Pd and Pt supported on the grain boundaries and surfaces of the cerium-zirconium composite oxide. 0.52 Zr 0.36 La 0.05 Y 0.07 The catalyst performance test was carried out on the sample, and the sample preparation steps and catalyst test conditions were the same as those in Comparative Example 1. The test results showed that the ignition temperature of CO was 290°C, the ignition temperature of NO was 320°C, and the ignition temperature of HC was 295°C.
[0046] Example 2 The cerium-zirconium composite oxide-supported precious metal catalyst PdPt / Ce prepared according to Example 1 0.52 Zr 0.36 La 0.05 Y 0.07200g of O2, an appropriate amount of alumina, and a certain amount of adhesive, acidity regulator, deionized water, etc. were mixed to prepare a coating slurry, and the slurry was prepared with a coating amount of 1.2g / L of the total amount of the honeycomb catalyst precious metals. The coated honeycomb carrier was then dried at 110°C for 4 hours, and the honeycomb carrier was further heat-treated at 300°C for 5 hours. Finally, the honeycomb carrier was roasted at 500°C for 5 hours to obtain a honeycomb-type precious metal catalyst, and the precious metals Pd and Pt were supported on the grain boundaries and surfaces of the cerium-zirconium composite oxide and alumina of the honeycomb-type precious metal catalyst. The catalyst performance test was performed on the sample, and the sample preparation steps and catalyst test conditions were the same as those of Comparative Example 2. The test results showed that the ignition temperature of CO was 270°C, the ignition temperature of NO was 300°C, and the ignition temperature of HC was 284°C.
[0047] Example 3 A certain volume of palladium nitrate and rhodium nitrate solution with a loading of 1.2% palladium and 0.2% rhodium was weighed and added to 200g of Ce. 0.16 Zr 0.78 La 0.02 Nd 0.04 The sample was mixed uniformly with O2 powder, dried at 110℃ for 4 hours, heat-treated at 550℃ for 4 hours, and finally roasted at 500℃ for 5 hours in a hydrogen atmosphere to obtain the catalyst sample PdRh / Ce with precious metals Pd and Rh supported on the grain boundary and surface of the cerium-zirconium composite oxide. 0.16 Zr 0.78 La 0.02 Nd 0.04 The catalyst performance test was carried out on the sample, and the sample preparation steps and catalyst test conditions were the same as those in Comparative Example 1. The test results showed that the ignition temperature of CO was 278°C, the ignition temperature of NO was 279°C, and the ignition temperature of HC was 313°C.
[0048] Example 4 The cerium zirconium composite oxide-supported precious metal catalyst PdRh / Ce prepared according to Example 3 0.16 Zr 0.78 La 0.02 Nd 0.04200g of O2, an appropriate amount of activated alumina, and a certain amount of adhesive, acidity regulator, deionized water, etc. are mixed to form a coating slurry, and the slurry is prepared with a coating amount of 1.4g / L of the total amount of the honeycomb catalyst precious metals. The coated honeycomb carrier is dried at 110°C for 4 hours, and the honeycomb carrier is further heat-treated at 300°C for 5 hours. Finally, the honeycomb carrier is roasted at 500°C for 5 hours to obtain a honeycomb-type precious metal catalyst, and the precious metals Pd and Rh are supported on the grain boundaries and surfaces of the cerium-zirconium composite oxide and alumina of the honeycomb-type precious metal catalyst. The catalyst performance test was performed on the sample, and the sample preparation steps and catalyst test conditions were the same as those of Comparative Example 2. The test results showed that the ignition temperature of CO was 261°C, the ignition temperature of NO was 250°C, and the ignition temperature of HC was 287°C.
[0049] Example 5 Palladium nitrate, platinum nitrate, and rhodium nitrate solutions with a fixed volume of 0.4% palladium, 0.3% platinum, and 0.01% rhodium were weighed out and mixed with 200g of Ce. 0.38 Zr 0.53 La 0.071 Pr 0.01 Y 0.01 The sample was uniformly mixed with O2 powder, and then dried at 110°C for 4 hours. The sample was then heat-treated at 550°C for 4 hours. Finally, the sample was reduced and roasted at 500°C for 4 hours in a hydrogen atmosphere to obtain the catalyst sample PdPtRh / Ce with precious metals Pd, Pt, and Rh supported on the grain boundary and surface of the cerium-zirconium composite oxide. 0.38 Zr 0.53 La 0.071 Pr 0.01 Y 0.01 The catalyst performance test was carried out on the sample, and the sample preparation steps and catalyst test conditions were the same as those in Comparative Example 1. The test results showed that the ignition temperature of CO was 260°C, the ignition temperature of NO was 287°C, and the ignition temperature of HC was 286°C.
[0050] Example 6 Palladium nitrate, platinum nitrate, and rhodium nitrate solutions with a fixed volume of 0.7% palladium, 0.2% platinum, and 0.1% rhodium were weighed out and mixed with 200g of Ce. 0.33 Zr0.58 La 0.033 Nd 0.032 Y 0.025 The sample was uniformly mixed with O2 powder, and then dried at 110°C for 4 hours. The sample was then heat-treated at 200°C for 4 hours. Finally, the sample was reduced and roasted at 500°C for 4 hours in a hydrogen atmosphere to obtain the catalyst sample PdPtRh / Ce with precious metals Pd, Pt, and Rh supported on the grain boundary and surface of the cerium-zirconium composite oxide. 0.33 Zr 0.58 La 0.033 Nd 0.032 Y 0.025 The catalyst performance test was carried out on the sample, and the sample preparation steps and catalyst test conditions were the same as those in Comparative Example 1. The test results showed that the ignition temperature of CO was 315°C, the ignition temperature of NO was 324°C, and the ignition temperature of HC was 327°C.
[0051] Example 7 Palladium nitrate, platinum nitrate, and rhodium nitrate solutions with a fixed volume of 0.7% palladium, 0.2% platinum, and 0.1% rhodium were weighed out and mixed with 200g of Ce. 0.33 Zr 0.58 La 0.033 Nd 0.032 Y 0.025 The sample was mixed uniformly with O2 powder, and then dried at 110°C for 4 hours. The sample was then heat-treated at 400°C for 4 hours. Finally, the sample was reduced and roasted at 500°C for 4 hours in a hydrogen atmosphere to obtain the catalyst sample PdPtRh / Ce with precious metals Pd, Pt, and Rh supported on the grain boundary and surface of the cerium-zirconium composite oxide. 0.33 Zr 0.58 La 0.033 Nd 0.032 Y 0.025 The catalyst performance test was carried out on the sample, and the sample preparation steps and catalyst test conditions were the same as those in Comparative Example 1. The test results showed that the ignition temperature of CO was 278°C, the ignition temperature of NO was 310°C, and the ignition temperature of HC was 290°C.
[0052] Example 8 Palladium nitrate, platinum nitrate, and rhodium nitrate solutions with a fixed volume of 0.7% palladium, 0.2% platinum, and 0.1% rhodium were weighed out and mixed with 200g of Ce. 0.33 Zr 0.58 La 0.033 Nd 0.032 Y 0.025 The sample was uniformly mixed with O2 powder, and then dried at 110°C for 4 hours. The sample was then heat-treated at 600°C for 4 hours. Finally, the sample was reduced and roasted at 500°C for 4 hours in a hydrogen atmosphere to obtain the catalyst sample PdPtRh / Ce with precious metals Pd, Pt, and Rh supported on the grain boundary and surface of the cerium-zirconium composite oxide. 0.33 Zr 0.58 La 0.033 Nd 0.032 Y 0.025 The catalyst performance test was carried out on the sample, and the sample preparation steps and catalyst test conditions were the same as those in Comparative Example 1. The test results showed that the ignition temperature of CO was 259°C, the ignition temperature of NO was 277°C, and the ignition temperature of HC was 278°C.
[0053] Example 9 The cerium-zirconium composite oxide-supported precious metal catalyst PdPtRh / Ce 0.33 Zr 0.58 La 0.033 Nd 0.032 Y 0.025 200g of O2, an appropriate amount of activated alumina, and a certain amount of adhesive, acidity regulator, deionized water, etc. were mixed to prepare a coating slurry, and the slurry was prepared with a coating amount of 1g / L of the total amount of the honeycomb catalyst precious metals. The coated honeycomb carrier was then dried at 110°C for 4 hours, and the honeycomb carrier was further heat-treated at 400°C for 12 hours. Finally, the honeycomb carrier was roasted at 500°C for 5 hours to obtain a honeycomb-type precious metal catalyst, and the precious metals Pd, Pt, and Rh were supported on the grain boundaries and surfaces of the cerium-zirconium composite oxide and alumina of the honeycomb-type precious metal catalyst. The catalyst performance test was performed on the sample, and the sample preparation steps and catalyst test conditions were the same as those of Comparative Example 2. The test results showed that the ignition temperature of CO was 257°C, the ignition temperature of NO was 283°C, and the ignition temperature of HC was 267°C.
[0054] Example 10 A certain volume of palladium, platinum, and rhodium chloride liquid salt with a loading of 0.7% palladium, 0.2% platinum, and 0.1% rhodium was weighed out and mixed with 200g of Ce. 0.33 Zr 0.58 La 0.033 Nd 0.032 Y 0.025 The sample was uniformly mixed with O2 powder, dried at 110°C for 4 hours, and then heat-treated for the first 4 hours at 450°C. Then, the sample was heat-treated for the second 4 hours at 800°C. Finally, the sample was reduced and roasted for 4 hours at 500°C in a hydrogen atmosphere. The catalyst sample PdPtRh / Ce with precious metals Pd, Pt, and Rh supported on the grain boundary and surface of the cerium-zirconium composite oxide was obtained. 0.33 Zr 0.58 La 0.033 Nd 0.032 Y 0.025 The catalyst performance test was carried out on the sample, and the sample preparation steps and catalyst test conditions were the same as those in Comparative Example 1. The test results showed that the ignition temperature of CO was 264°C, the ignition temperature of NO was 291°C, and the ignition temperature of HC was 275°C.
[0055] Example 11 200g of activated alumina and a certain amount of adhesive, acidity regulator, deionized water, etc. are mixed to prepare a coating slurry, and the alumina slurry is coated on a ceramic honeycomb carrier so that the honeycomb carrier contains 100g / L of alumina. The coated honeycomb carrier is dried at 110°C for 4 hours to obtain the cerium zirconium composite oxide-supported precious metal catalyst PdPtRh / Ce 0.33 Zr 0.58 La 0.033 Nd 0.032 Y 0.025200g of O2 and a certain amount of adhesive, acidity regulator, deionized water, etc. were mixed to prepare a coating slurry, and the slurry was prepared with a coating amount of 1g / L of the total amount of the honeycomb catalyst precious metals. The coated honeycomb carrier was dried at 110°C for 4 hours, and then the honeycomb carrier was heat-treated at 600°C for 4 hours. Finally, the honeycomb carrier was roasted at 500°C for 5 hours to obtain a honeycomb-type precious metal catalyst. The precious metals Pd, Pt, and Rh were mainly supported on the grain boundaries and surfaces of the cerium zirconium composite oxide of the honeycomb-type precious metal catalyst, and a small amount was supported on the grain boundaries and surfaces of the cerium zirconium composite oxide and alumina. The catalyst performance test was performed on the sample. The sample preparation steps and catalyst test conditions were the same as those of Comparative Example 2. The test results showed that the ignition temperature of CO was 267°C, the ignition temperature of NO was 279°C, and the ignition temperature of HC was 274°C.
[0056] Example 12 A certain volume of liquid acetate of palladium and rhodium with a loading of 0.8% palladium and 0.08% rhodium was weighed out to obtain a cerium-zirconium composite oxide (Ce) with a core-shell structure whose surface is rich in yttrium. 0.18 Zr 0.64 La 0.03 Y 0.15 The sample was uniformly mixed with 200 g of O2 powder, dried at 110 °C for 4 hours, and then heat-treated for the first time at 600 °C for 6 hours. Then, the sample was heat-treated for the second time at 580 °C for 5 hours to obtain the catalyst sample PdRh / Ce with precious metals Pd and Rh supported on the grain boundary and surface of the cerium-zirconium composite oxide. 0.18 Zr 0.64 La 0.03 Y 0.15 The catalyst performance test was carried out on the sample, and the sample preparation steps and catalyst test conditions were the same as those in Comparative Example 1. The test results showed that the ignition temperature of CO was 251°C, the ignition temperature of NO was 264°C, and the ignition temperature of HC was 239°C.
[0057] (Example 13) Grain boundary and surface-supported precious metal catalyst PdRh / Ce of cerium-zirconium composite oxide prepared according to Example 12 0.18 Zr0.64 La 0.03 Y 0.15 200g of O2, an appropriate amount of activated alumina, and a certain amount of adhesive, acidity regulator, deionized water, etc. are mixed to form a coating slurry, and the slurry is prepared with a coating amount of 0.88g / L of the total amount of the honeycomb catalyst precious metals. The coated honeycomb carrier is then dried at 110°C for 4 hours, and the honeycomb carrier is further heat-treated at 600°C for 6 hours. Finally, the honeycomb carrier is roasted at 580°C for 5 hours to obtain a honeycomb-type precious metal catalyst, and the precious metals Pd and Rh are supported on the grain boundaries and surfaces of the cerium-zirconium composite oxide and alumina of the honeycomb-type precious metal catalyst. The catalyst performance test was performed on the sample, and the sample preparation steps and catalyst test conditions were the same as those of Comparative Example 2. The test results showed that the ignition temperature of CO was 243°C, the ignition temperature of NO was 250°C, and the ignition temperature of HC was 235°C.
[0058] Example 14 A certain volume of liquid acetate of platinum and rhodium with a loading of 0.3% platinum and 0.02% rhodium was weighed out and a gradient cerium-zirconium composite oxide (Ce) rich in cerium was formed on the surface. 0.33 Zr 0.57 La 0.04 Y 0.06 The sample was uniformly mixed with 200 g of O2 powder, dried at 110 °C for 4 hours, and then heat-treated for the first time at 550 °C for 4 hours. The sample was then heat-treated for the second time at 500 °C for 5 hours to obtain the catalyst sample PtRh / Ce with precious metals Pt and Rh supported on the grain boundaries and surfaces of the cerium-zirconium composite oxide. 0.33 Zr 0.57 La 0.04 Y 0.06 The catalyst performance test was carried out on the sample, and the sample preparation steps and catalyst test conditions were the same as those in Comparative Example 1. The test results showed that the ignition temperature of CO was 241°C, the ignition temperature of NO was 246°C, and the ignition temperature of HC was 251°C.
[0059] Example 15 Cerium-zirconium composite oxide-supported precious metal catalyst PtRh / Ce prepared according to Example 14 0.33 Zr 0.57 La0.04 Y 0.06 200g of O2, an appropriate amount of activated alumina, a certain amount of adhesive, acidity regulator, deionized water, etc. are mixed to form a coating slurry, and the slurry is prepared with a coating amount of 0.32g / L of the total amount of the honeycomb catalyst precious metals. The coated honeycomb carrier is dried at 110°C for 4 hours, and the honeycomb carrier is further heat-treated at 550°C for 4 hours. Finally, the honeycomb carrier is roasted at 500°C for 5 hours to obtain a honeycomb-type precious metal catalyst, and the precious metals Pt and Rh are supported on the grain boundaries and surfaces of the cerium-zirconium composite oxide and alumina of the honeycomb-type precious metal catalyst. The catalyst performance test was performed on the sample, and the sample preparation steps and catalyst test conditions were the same as those of Comparative Example 2. The test results showed that the ignition temperature of CO was 235°C, the ignition temperature of NO was 230°C, and the ignition temperature of HC was 243°C.
[0060] (Example 16) A certain volume of liquid nitrate of palladium and platinum with a loading of 0.2% palladium and 0.5% platinum was weighed out to obtain a cerium-zirconium composite oxide (Ce) with a core-shell structure whose surface is rich in cerium-yttrium. 0.42 Zr 0.47 La 0.045 Y 0.064 The sample was uniformly mixed with 200 g of O2 powder, dried at 110 °C for 4 hours, and then heat-treated for the first time at 610 °C for 7 hours. The sample was then heat-treated for the second time at 470 °C for 4 hours to obtain the catalyst sample PdPt / Ce with precious metals Pd and Pt supported on the grain boundaries and surface of the cerium-zirconium composite oxide. 0.42 Zr 0.47 La 0.045 Y 0.064 The catalyst performance test was carried out on the sample, and the sample preparation steps and catalyst test conditions were the same as those in Comparative Example 1. The test results showed that the ignition temperature of CO was 243°C, the ignition temperature of NO was 259°C, and the ignition temperature of HC was 239°C.
[0061] (Example 17) Cerium-zirconium composite oxide-supported precious metal catalyst PdPt / Ce prepared according to Example 16 0.42 Zr 0.47 La0.045 Y 0.064 200g of O2, an appropriate amount of activated alumina, a certain amount of adhesive, acidity regulator, deionized water, etc. are mixed to form a coating slurry, and the slurry is prepared with a coating amount of 0.7g / L of the total amount of the honeycomb catalyst precious metals. The coated honeycomb carrier is dried at 110°C for 4 hours, and the honeycomb carrier is further heat-treated at 490°C for 7 hours. Finally, the honeycomb carrier is roasted at 570°C for 4 hours to obtain a honeycomb-type precious metal catalyst, and the precious metals Pd and Pt are supported on the grain boundaries and surfaces of the cerium-zirconium composite oxide and alumina of the honeycomb-type precious metal catalyst. The catalyst performance test was performed on the sample, and the sample preparation steps and catalyst test conditions were the same as those of Comparative Example 2. The test results showed that the ignition temperature of CO was 237°C, the ignition temperature of NO was 248°C, and the ignition temperature of HC was 227°C.
[0062] (Example 18) A certain volume of liquid nitrate of palladium and rhodium with a loading of 0.1% palladium and 0.02% rhodium was weighed out to obtain a cerium-zirconium composite oxide (Ce) with a core-shell structure with a neodymium-rich surface. 0.24 Zr 0.7 La 0.017 Nd 0.043 The sample was uniformly mixed with 200 g of O2 powder, dried at 110 °C for 4 hours, and then heat-treated for the first time at 520 °C for 3 hours. The sample was then heat-treated for the second time at 630 °C for 6 hours to obtain the catalyst sample PdRh / Ce with precious metals Pd and Rh supported on the grain boundaries and surface of the cerium-zirconium composite oxide. 0.24 Zr 0.7 La 0.017 Nd 0.043 The catalyst performance test was carried out on the sample, and the sample preparation steps and catalyst test conditions were the same as those in Comparative Example 1. The test results showed that the ignition temperature of CO was 233°C, the ignition temperature of NO was 211°C, and the ignition temperature of HC was 225°C.
[0063] (Example 19) Cerium-zirconium composite oxide-supported precious metal catalyst PdRh / Ce prepared according to Example 18 0.24 Zr 0.7 La0.017 Nd 0.043 200g of O2, an appropriate amount of activated alumina, a certain amount of adhesive, acidity regulator, deionized water, etc. are mixed to form a coating slurry, and the slurry is prepared with a coating amount of 0.12g / L of the total amount of precious metals in the honeycomb catalyst. The coated honeycomb carrier is dried at 110°C for 4 hours, and then the honeycomb carrier is heat-treated at 510°C for 3 hours. Finally, the honeycomb carrier is roasted at 600°C for 5 hours to obtain a honeycomb-type precious metal catalyst, and the precious metals Pd and Rh are supported on the grain boundaries and surfaces of the cerium-zirconium composite oxide and alumina of the honeycomb-type precious metal catalyst. The catalyst performance test was carried out on the sample, and the sample preparation steps and catalyst test conditions were the same as those of Comparative Example 2. The test results showed that the ignition temperature of CO was 230°C, the ignition temperature of NO was 205°C, and the ignition temperature of HC was 222°C.
[0064] (Example 20) A certain volume of palladium nitrate and platinum nitrate solution with palladium 1% and platinum 0.01% loading was mixed uniformly with 200g of CeO2 powder, and the sample was dried at 110℃ for 4 hours, further heat-treated at 500℃ for 4.5 hours, and finally reduced and roasted at 400℃ for 24 hours in a hydrogen atmosphere to obtain a catalyst sample PdPt / CeO2 with precious metals Pd and Pt loaded on the grain boundaries and surface of cerium oxide. The catalyst performance test was carried out on the sample, and the sample preparation steps and catalyst test conditions were the same as those of Comparative Example 1. The test results showed that the ignition temperature of CO was 304℃, the ignition temperature of NO was 339℃, and the ignition temperature of HC was 317℃.
[0065] Example 21 The cerium oxide-supported precious metal catalyst PdPt / CeO2 prepared according to Example 20, 200g, an appropriate amount of activated alumina, and a certain amount of adhesive, acidity regulator, deionized water, etc. were mixed to form a coating slurry, and the slurry was prepared with a coating amount of 0.61g / L of the total loading amount of the honeycomb catalyst precious metals, and coated on a ceramic honeycomb carrier, and the coated honeycomb carrier was dried at 110°C for 4 hours, and then the honeycomb carrier was heat-treated at 300°C for 18 hours, and finally the honeycomb carrier was roasted at 400°C for 12 hours to obtain a honeycomb-type precious metal catalyst, and the precious metals Pd and Pt were supported on the grain boundaries and surfaces of the cerium oxide and alumina of the honeycomb-type precious metal catalyst. The catalytic performance test was carried out on the sample, and the sample preparation steps and catalytic test conditions were the same as those of Comparative Example 2. The test results showed that the ignition temperature of CO was 288°C, the ignition temperature of NO was 329°C, and the ignition temperature of HC was 303°C.
[0066] Example 22 A fixed volume of acetate solution of palladium and rhodium with a loading of 1.2% palladium and 0.08% rhodium was added to 200g of Ce. 0.38 Zr 0.53 La 0.045 Sm 0.03 Tm 0.015 The sample was uniformly mixed with O2 powder, dried at 110℃ for 4 hours, and then heat-treated at 600℃ for 4 hours. The sample was then subjected to the first reduction roasting at 500℃ for 5 hours in a hydrogen atmosphere, and finally the sample was subjected to the second reduction roasting at 650℃ for 2 hours in a hydrogen atmosphere to obtain the catalyst sample PdRh / Ce with precious metals Pd and Rh supported on the grain boundaries and surface of the cerium-zirconium composite oxide. 0.38 Zr 0.53 La 0.045 Sm 0.03 Tm 0.015 The catalyst performance test was carried out on the sample, and the sample preparation steps and catalyst test conditions were the same as those in Comparative Example 1. The test results showed that the ignition temperature of CO was 254°C, the ignition temperature of NO was 257°C, and the ignition temperature of HC was 260°C.
[0067] (Example 23) A fixed volume of platinum nitrate and rhodium nitrate solution with platinum 1.9% and rhodium 0.1% loading was added to 200g of Ce. 0.13 Zr 0.64 La 0.03 Nd 0.03 Mn 0.17 The sample was mixed uniformly with O2 powder, dried at 110°C for 4 hours, heat-treated at 200°C for 24 hours, and finally roasted at 700°C in a CO atmosphere for 0.5 hours to obtain the catalyst sample PtRh / Ce with precious metals Pt and Rh supported on the grain boundaries and surfaces of the cerium-zirconium composite oxide. 0.13 Zr 0.64 La 0.03 Nd 0.03 Mn 0.17 The catalyst performance test was carried out on the sample, and the sample preparation steps and catalyst test conditions were the same as those in Comparative Example 1. The test results showed that the ignition temperature of CO was 286°C, the ignition temperature of NO was 280°C, and the ignition temperature of HC was 293°C.
[0068] Example 24 Cerium-zirconium composite oxide-supported precious metal catalyst PdRh / Ce prepared according to Example 23 0.38 Zr 0.53 La 0.045 Sm 0.03 Tm 0.015 The cerium-zirconium composite oxide-supported precious metal catalyst PtRh / Ce prepared in Example 15 was prepared by coating 200 g of O2, an appropriate amount of activated alumina, a certain amount of adhesive, an acidity regulator, deionized water, etc. to prepare a slurry a. 0.13 Zr 0.64 La 0.03 Nd 0.03 Mn 0.17Another coating slurry b was prepared by mixing 200g of O2, an appropriate amount of activated alumina, and a certain amount of adhesive, acidity regulator, deionized water, etc., and coating the slurry a on half of the honeycomb carrier with a coating amount of 0.64g / L of total precious metals. The honeycomb carrier with the half coating was dried at 110°C for 4 hours. The remaining honeycomb carrier was coated with the slurry b on the other half of the honeycomb carrier with a coating amount of 1g / L of total precious metals. The coated honeycomb carrier was dried at 110°C for 4 hours. The honeycomb carrier was then heat-treated at 450°C for 3 hours. Finally, the honeycomb carrier was roasted at 550°C for 6 hours to obtain a honeycomb-type precious metal catalyst with a total precious metal loading of 1.64g / L. The precious metals Pd, Pt, and Rh were supported on the grain boundaries and surfaces of the cerium-zirconium composite oxide and alumina of the honeycomb-type precious metal catalyst. A catalytic performance test was conducted on the sample. The sample preparation steps and catalytic test conditions were the same as those in Comparative Example 2. The test results showed that the ignition temperature of CO was 245°C, the ignition temperature of NO was 249°C, and the ignition temperature of HC was 247°C.
[0069] (Example 25) A volume of rhodium nitrate solution with a rhodium loading of 0.01% was added to 200 g of Ce. 0.78 Zr 0.16 La 0.02 Y 0.02 Fe 0.02 The sample was mixed uniformly with O2 powder, dried at 110°C for 4 hours, heat-treated at 300°C for 20 hours, roasted at 450°C for 4 hours in an air atmosphere, and finally roasted at 570°C for 5 hours in a hydrogen atmosphere to obtain the catalyst sample Rh / Ce with precious metal rhodium supported on the grain boundary and surface of the cerium-zirconium composite oxide. 0.78 Zr 0.16 La 0.02 Y 0.02 Fe 0.02 The catalyst performance test was carried out on the sample, and the sample preparation steps and catalyst test conditions were the same as those in Comparative Example 1. The test results showed that the ignition temperature of CO was 313°C, the ignition temperature of NO was 291°C, and the ignition temperature of HC was 305°C.
[0070] (Example 26) The cerium zirconium composite oxide-supported precious metal catalyst Rh / Ce prepared according to Example 25 0.78 Zr 0.16 La 0.02 Y 0.02 Fe 0.02 200g of O2, an appropriate amount of activated alumina, a certain amount of adhesive, acidity regulator, deionized water, etc. are mixed to form a coating slurry, and the slurry is prepared with a coating amount of 0.01g / L of the total amount of the honeycomb catalyst precious metal. The coated honeycomb carrier is then dried at 110°C for 4 hours, and finally the honeycomb carrier is roasted at 500°C for 5 hours to obtain a honeycomb-type precious metal catalyst, in which the precious metal Rh is supported on the grain boundaries and surfaces of the cerium-zirconium composite oxide and alumina of the honeycomb-type precious metal catalyst. The catalytic performance test of the sample is carried out. The sample preparation steps and catalytic test conditions are the same as those of Comparative Example 2. The test results show that the ignition temperature of CO is 296°C, the ignition temperature of NO is 281°C, and the ignition temperature of HC is 293°C.
[0071] Example 27 A certain volume of palladium nitrate solution with a palladium loading of 0.5% was weighed out and 200 g of Ce was added. 0.38 Zr 0.5 La 0.07 Pr 0.03 Y 0.01 S 0.01 O 1.999 N 0.001 and 200g of activated alumina powder were mixed uniformly, and the sample was dried at 110°C for 4 hours, and then heat-treated at 550°C for 3 hours. Finally, the sample was reduced and roasted at 470°C for 16 hours in a hydrogen atmosphere to obtain the catalyst sample Pd / Ce with precious metal supported on the grain boundary and surface of the cerium-zirconium composite oxide and alumina. 0.38 Zr 0.5 La 0.07 Pr 0.03 Y 0.01 S 0.01 O 1.999 N 0.001&Al2O3 was obtained. A catalytic performance test was carried out on the sample, and the sample preparation steps and catalytic test conditions were the same as those in Comparative Example 1. The test results showed that the ignition temperature of CO was 265°C, the ignition temperature of NO was 270°C, and the ignition temperature of HC was 270°C.
[0072] (Example 28) Cerium-zirconium composite oxide and alumina-supported noble metal catalyst Pd / Ce prepared according to Example 27 0.38 Zr 0.5 La 0.07 Pr 0.03 Y 0.01 S 0.01 O 1.999 N 0.001 200g of &Al2O3 and an appropriate amount of adhesive, acidity regulator, deionized water, etc. were mixed to prepare a coating slurry, and the slurry was prepared with a coating amount of 1g / L of the total amount of the honeycomb catalyst precious metals, and then coated on a ceramic honeycomb carrier, and the coated honeycomb carrier was dried at 110°C for 4 hours, and then the honeycomb carrier was heat-treated at 750°C for 1 hour, and finally the honeycomb carrier was roasted at 600°C for 5 hours to obtain a honeycomb-type precious metal catalyst, and the precious metal Pd was supported on the grain boundaries and surfaces of the cerium-zirconium composite oxide and alumina of the honeycomb-type precious metal catalyst. The catalyst performance test was carried out on the sample, and the sample preparation steps and catalyst test conditions were the same as those of Comparative Example 2. The test results showed that the ignition temperature of CO was 260°C, the ignition temperature of NO was 263°C, and the ignition temperature of HC was 258°C.
[0073] (Example 29) A fixed volume of palladium nitrate and platinum nitrate solution with a loading of 0.5% palladium and 1.8% platinum was added to 200 g of Ce. 0.18 Zr 0.64 La 0.03 Y 0.13 Yb 0.02 O 1.995 F 0.005 The powder was mixed uniformly, and the sample was dried at 110°C for 4 hours. The sample was then heat-treated at 600°C for 4 hours. Finally, the sample was reduced and roasted at 600°C for 4 hours in a hydrogen atmosphere to obtain the catalyst sample PdPt / Ce with precious metals Pd and Pt supported on the grain boundaries and surface of the cerium-zirconium composite oxide.0.18 Zr 0.64 La 0.03 Y 0.13 Yb 0.02 O 1.995 F 0.005 The catalyst performance test was carried out on the sample, and the sample preparation steps and catalyst test conditions were the same as those of Comparative Example 1. The test results showed that the ignition temperature of CO was 243°C, the ignition temperature of NO was 261°C, and the ignition temperature of HC was 242°C.
[0074] (Example 30) A fixed volume of platinum nitrate and rhodium nitrate solution with platinum 0.9% and rhodium 0.01% loading was added to 200g of Ce. 0.33 Zr 0.5 La 0.033 Nd 0.032 Y 0.025 Sr 0.04 Ba 0.04 The sample was mixed uniformly with O2 powder, dried at 110°C for 4 hours, heat-treated at 600°C for 6.5 hours, and finally roasted at 500°C for 12 hours in a hydrogen atmosphere to obtain the catalyst sample PtRh / Ce with precious metals Pt and Rh supported on the grain boundaries and surfaces of the cerium-zirconium composite oxide. 0.33 Zr 0.5 La 0.033 Nd 0.032 Y 0.025 Sr 0.04 Ba 0.04 The catalyst performance test was carried out on the sample, and the sample preparation steps and catalyst test conditions were the same as those in Comparative Example 1. The test results showed that the ignition temperature of CO was 256°C, the ignition temperature of NO was 261°C, and the ignition temperature of HC was 263°C.
[0075] (Example 31) The cerium-zirconium composite oxide-supported precious metal catalyst PtRh / Ce was prepared according to Example 30 with a cerium-zirconium content of 90% and an alumina content of 10% in the honeycomb-type precious metal catalyst coating. 0.33 Zr 0.5 La 0.033 Nd 0.032 Y 0.025 Sr 0.04 Ba 0.04200g of O2, an appropriate amount of activated alumina, and a certain amount of adhesive, acidity regulator, deionized water, etc. are mixed to form a coating slurry, and the slurry is prepared with a coating amount of 1.64g / L of the total amount of the honeycomb catalyst precious metals. The coated honeycomb carrier is dried at 110°C for 4 hours, and the honeycomb carrier is further heat-treated at 800°C for 0.5 hours. Finally, the honeycomb carrier is roasted at 700°C for 0.5 hours to obtain a honeycomb-type precious metal catalyst, and the precious metals Pt and Rh are supported on the grain boundaries and surfaces of the cerium-zirconium composite oxide and alumina of the honeycomb-type precious metal catalyst. The catalytic performance test of the sample is performed. The sample preparation steps and catalyst test conditions are the same as those of Comparative Example 2. The test results show that the ignition temperature of CO is 265°C, the ignition temperature of NO is 271°C, and the ignition temperature of HC is 274°C.
[0076] Example 32 A fixed volume of platinum nitrate and rhodium nitrate solution with platinum 0.5% and rhodium 0.4% loading was added to 200g of Ce 0.16 Zr 0.6 La 0.02 Nd 0.04 Mn 0.12 Ba 0.06 The sample was mixed uniformly with O2 powder, dried at 110℃ for 4 hours, heat-treated at 700℃ for 8 hours, and finally roasted at 600℃ for 4 hours in a hydrogen atmosphere to obtain the catalyst sample PtRh / Ce with precious metals Pt and Rh supported on the grain boundaries and surfaces of the cerium-zirconium composite oxide. 0.16 Zr 0.6 La 0.02 Nd 0.04 Mn 0.12 Ba 0.06 The catalyst performance test was carried out on the sample, and the sample preparation steps and catalyst test conditions were the same as those in Comparative Example 1. The test results showed that the ignition temperature of CO was 251°C, the ignition temperature of NO was 248°C, and the ignition temperature of HC was 260°C.
[0077] (Example 33) Cerium-zirconium composite oxide-supported precious metal catalyst PtRh / Ce prepared according to Example 32 0.16 Zr 0.6 La0.02 Nd 0.04 Mn 0.12 Ba 0.06 200g of O2, an appropriate amount of activated alumina, and a certain amount of adhesive, acidity regulator, deionized water, etc. were mixed to prepare a coating slurry, and the slurry was prepared with a coating amount of 1.08g / L of the total amount of the honeycomb catalyst precious metals. The coated honeycomb carrier was then dried at 110°C for 4 hours, and the honeycomb carrier was further heat-treated at 430°C for 3 hours. Finally, the honeycomb carrier was roasted at 650°C for 6 hours to obtain a honeycomb-type precious metal catalyst, and the precious metals Pt and Rh were supported on the grain boundaries and surfaces of the cerium-zirconium composite oxide and alumina of the honeycomb-type precious metal catalyst. The catalyst performance test was carried out on the sample, and the sample preparation steps and catalyst test conditions were the same as those of Comparative Example 2. The test results showed that the ignition temperature of CO was 247°C, the ignition temperature of NO was 242°C, and the ignition temperature of HC was 253°C.
[0078] (Example 34) A volume of rhodium nitrate solution with a rhodium loading of 0.1% was added to 200 g of Zr 0.86 La 0.09 Y 0.04 Ti 0.01 The sample was uniformly mixed with O2 powder, and then dried at 110°C for 4 hours. The sample was then heat-treated at 420°C for 6 hours. Finally, the sample was reduced and roasted at 630°C for 4 hours in a hydrogen atmosphere to obtain the catalyst sample Rh / ZrO2, which supports the precious metal Rh on the grain boundaries and surfaces of the cerium-zirconium composite oxide. 0.86 La 0.09 Y 0.04 Ti 0.01 The catalyst performance test was carried out on the sample, and the sample preparation steps and catalyst test conditions were the same as those in Comparative Example 1. The test results showed that the ignition temperature of CO was 271°C, the ignition temperature of NO was 248°C, and the ignition temperature of HC was 277°C.
[0079] (Example 35) The cerium-zirconium composite oxide-supported precious metal catalyst Rh / Zr prepared according to Example 34 with a cerium-zirconium content of 70% and an alumina content of 30% in the honeycomb-type precious metal catalyst coating. 0.86 La0.09 Y 0.04 Ti 0.01 200g of O2, an appropriate amount of activated alumina, a certain amount of adhesive, acidity regulator, deionized water, etc. are mixed to form a coating slurry, and the slurry is prepared with a coating amount of 0.14g / L of the total amount of precious metals in the honeycomb catalyst. The coated honeycomb carrier is dried at 110°C for 4 hours, and then the honeycomb carrier is heat-treated at 550°C for 3 hours. Finally, the honeycomb carrier is roasted at 700°C for 1.5 hours to obtain a honeycomb-type precious metal catalyst, and the precious metal rhodium is supported on the grain boundaries and surfaces of the cerium-zirconium composite oxide and alumina of the honeycomb-type precious metal catalyst. The catalytic performance test of the sample is performed. The sample preparation steps and catalytic test conditions are the same as those of Comparative Example 2. The test results show that the ignition temperature of CO is 268°C, the ignition temperature of NO is 233°C, and the ignition temperature of HC is 272°C.
[0080] (Example 36) A volume of rhodium nitrate solution with a rhodium loading of 0.1% was added to 200 g of Zr 0.86 La 0.095 Y 0.045 The sample was uniformly mixed with O2 powder, and then dried at 110°C for 4 hours. The sample was then heat-treated at 630°C for 5 hours. Finally, the sample was reduced and roasted at 700°C for 5 hours in a hydrogen atmosphere to obtain the catalyst sample Rh / ZrO2, which supports the precious metal Rh on the grain boundaries and surfaces of the cerium-zirconium composite oxide. 0.86 La 0.095 Y 0.045 The catalyst performance test was carried out on the sample, and the sample preparation steps and catalyst test conditions were the same as those in Comparative Example 1. The test results showed that the ignition temperature of CO was 270°C, the ignition temperature of NO was 264°C, and the ignition temperature of HC was 274°C.
[0081] (Example 37) The cerium-zirconium composite oxide-supported precious metal catalyst Rh / Zr prepared according to Example 34 with a cerium-zirconium content of 70% and an alumina content of 30% in the honeycomb-type precious metal catalyst coating. 0.86 La 0.095 Y 0.045200g of O2, an appropriate amount of activated alumina, a certain amount of adhesive, acidity regulator, deionized water, etc. are mixed to form a coating slurry, and the slurry is prepared with a coating amount of 0.14g / L of the total amount of precious metals in the honeycomb catalyst. The coated honeycomb carrier is dried at 110°C for 4 hours, and then the honeycomb carrier is heat-treated at 600°C for 3 hours. Finally, the honeycomb carrier is roasted at 660°C for 5 hours to obtain a honeycomb-type precious metal catalyst, and the precious metal rhodium is supported on the grain boundaries and surfaces of the cerium-zirconium composite oxide and alumina of the honeycomb-type precious metal catalyst. The catalytic performance test was carried out on the sample, and the sample preparation steps and catalytic test conditions were the same as those of Comparative Example 2. The test results showed that the ignition temperature of CO was 265°C, the ignition temperature of NO was 251°C, and the ignition temperature of HC was 268°C.
[0082] (Example 38) Palladium nitrate, platinum nitrate, and rhodium nitrate solutions with a loading of 0.1% palladium, 0.2% platinum, and 0.1% rhodium were mixed with 200 g of Ce. 0.25 Zr 0.6 La 0.05 Y 0.05 Nb 0.02 Sn 0.03 The sample was uniformly mixed with O2 powder, and then dried at 110°C for 4 hours. The sample was then heat-treated at 620°C for 4 hours. Finally, the sample was reduced and roasted at 520°C for 7 hours in a hydrogen atmosphere to obtain the catalyst sample PdPtRh / Ce with the precious metals Pd, Pt, and Rh supported on the grain boundaries and surfaces of the cerium-zirconium composite oxide. 0.25 Zr 0.6 La 0.05 Y 0.05 Nb 0.02 Sn 0.03 The catalyst performance test was carried out on the sample, and the sample preparation steps and catalyst test conditions were the same as those in Comparative Example 1. The test results showed that the ignition temperature of CO was 276°C, the ignition temperature of NO was 257°C, and the ignition temperature of HC was 273°C.
[0083] (Example 39) A volume of rhodium nitrate solution with a rhodium loading of 0.1% was added to 200 g of Ce. 0.18 Zr 0.62 La0.03 Y 0.13 Er 0.02 Ni 0.02 The sample was uniformly mixed with O2 powder, and then dried at 110°C for 4 hours. The sample was then heat-treated at 710°C for 2 hours. Finally, the sample was reduced and roasted at 650°C for 3 hours in a hydrogen atmosphere to obtain the catalyst sample Rh / Ce, which supports the precious metal Rh on the grain boundaries and surfaces of the cerium-zirconium composite oxide. 0.18 Zr 0.62 La 0.03 Y 0.13 Er 0.02 Ni 0.02 The catalyst performance test was carried out on the sample, and the sample preparation steps and catalyst test conditions were the same as those in Comparative Example 1. The test results showed that the ignition temperature of CO was 291°C, the ignition temperature of NO was 258°C, and the ignition temperature of HC was 285°C.
[0084] (Example 40) Palladium nitrate and platinum nitrate solutions with a loading of 0.9% palladium and 0.5% platinum were added to 200g of Al. 0.48 Ce 0.175 Zr 0.3 La 0.018 Nd 0.018 Y 0.009 The sample was uniformly mixed with O2 powder, and then dried at 110°C for 4 hours. The sample was then heat-treated at 650°C for 5 hours. Finally, the sample was reduced and roasted at 500°C for 5 hours in a hydrogen atmosphere to obtain the catalyst sample PdPt / Al with precious metals Pd and Pt supported on the grain boundaries and surface of the cerium-zirconium composite oxide. 0.48 Ce 0.175 Zr 0.3 La 0.018 Nd 0.018 Y 0.009 The catalyst performance test was carried out on the sample, and the sample preparation steps and catalyst test conditions were the same as those in Comparative Example 1. The test results showed that the ignition temperature of CO was 273°C, the ignition temperature of NO was 285°C, and the ignition temperature of HC was 277°C.
[0085] (Example 41) The cerium zirconium composite oxide-supported precious metal catalyst PdPt / Al prepared according to Example 40 0.48 Ce0.175 Zr 0.3 La 0.018 Nd 0.018 Y 0.009 200g of O2, an appropriate amount of activated alumina, and a certain amount of adhesive, acidity regulator, deionized water, etc. are mixed to form a coating slurry, and the slurry is prepared with a coating amount of 1.4g / L of the total amount of the honeycomb catalyst precious metals. The coated honeycomb carrier is dried at 110°C for 4 hours, and the honeycomb carrier is further heat-treated at 250°C for 4 hours. Finally, the honeycomb carrier is roasted at 470°C for 16 hours to obtain a honeycomb-type precious metal catalyst, and the precious metals Pd and Pt are supported on the grain boundaries and surfaces of the cerium-zirconium composite oxide and alumina of the honeycomb-type precious metal catalyst. The catalyst performance test was performed on the sample, and the sample preparation steps and catalyst test conditions were the same as those of Comparative Example 2. The test results showed that the ignition temperature of CO was 253°C, the ignition temperature of NO was 264°C, and the ignition temperature of HC was 269°C.
[0086] (Example 42) Palladium nitrate and platinum nitrate solutions with a fixed volume of 0.01% palladium and 2% platinum were added to 200g of Ce. 0.30 Zr 0.61 La 0.044 Gd 0.04 Cu 0.006 The sample was uniformly mixed with O2 powder, and then dried at 110°C for 4 hours. The sample was then heat-treated at 270°C for 12 hours. The sample was then roasted for the first time at 440°C in an air atmosphere for 3 hours. Finally, the sample was roasted for the second time at 620°C in an air atmosphere for 3 hours to obtain the catalyst sample PdPt / Ce with precious metals Pd and Pt supported on the grain boundaries and surfaces of the cerium-zirconium composite oxide. 0.30 Zr 0.61 La 0.044 Gd 0.04 Cu 0.006 The catalyst performance test was carried out on the sample, and the sample preparation steps and catalyst test conditions were the same as those of Comparative Example 1. The test results showed that the ignition temperature of CO was 283°C, the ignition temperature of NO was 272°C, and the ignition temperature of HC was 278°C.
[0087] (Example 43) A certain volume of platinum nitrate solution with a platinum loading of 0.5% was uniformly mixed with 200 g of activated alumina powder, and the sample was dried at 110°C for 4 hours, further heat-treated at 350°C for 7 hours, and finally reduced and roasted at 500°C under a hydrogen atmosphere for 5 hours to obtain a catalyst sample Pt / Al2O3 with precious metal Pt loaded on the alumina grain boundaries and surface. The mass ratio of Pt / Al2O3 to cerium zirconium powder was 4:1. 0.13 Zr 0.64 La 0.03 Nd 0.03 Mn 0.17 The mixture of 80g of O2 and a certain amount of adhesive, acidity regulator, deionized water, etc. was mixed to prepare a coating slurry, and the above-prepared slurry was coated on a honeycomb carrier in a coating amount of 0.8g / L of the total amount of the honeycomb catalyst precious metal. The coated honeycomb carrier was dried at 110°C for 4 hours, and then heat-treated at 270°C for 7 hours. Finally, the honeycomb carrier was roasted at 500°C for 5 hours to obtain a honeycomb-type precious metal catalyst, and the precious metal Pt was supported on the grain boundaries and surfaces of the cerium-zirconium composite oxide and alumina of the honeycomb-type precious metal catalyst. The catalyst performance test was performed on the sample, and the sample preparation steps and catalyst test conditions were the same as those of Comparative Example 2. The test results showed that the ignition temperature of CO was 277°C, the ignition temperature of NO was 273°C, and the ignition temperature of HC was 281°C.
[0088] (Example 44) Cerium-zirconium composite oxide-supported precious metal catalyst PtRh / Ce prepared according to Example 23 0.13 Zr 0.64 La 0.03 Nd 0.03 Mn 0.17 Take 200 g of Pt / Al2O3 prepared according to Example 43, and add 200 g of PtRh / Ce 0.13 Zr 0.64 La 0.03 Nd 0.03 Mn 0.17O2 and Pt / Al2O3 and a certain amount of adhesive, acidity regulator, deionized water, etc. were mixed to form a coating slurry, and the slurry was prepared with a coating amount of 2.5g / L of the total amount of the honeycomb catalyst precious metals. The coated honeycomb carrier was dried at 110°C for 4 hours, and then the honeycomb carrier was heat-treated at 400°C for 3 hours. Finally, the honeycomb carrier was roasted at 550°C for 6 hours to obtain a honeycomb-type precious metal catalyst, and the precious metals Pt and Rh were supported on the grain boundaries and surfaces of the cerium-zirconium composite oxide and alumina of the honeycomb-type precious metal catalyst. The catalyst performance test was performed on the sample, and the sample preparation steps and catalyst test conditions were the same as those of Comparative Example 2. The test results showed that the ignition temperature of CO was 253°C, the ignition temperature of NO was 249°C, and the ignition temperature of HC was 255°C.
[0089] (Example 45) 200 g of Pt / Al2O3 prepared according to Example 43 and a certain amount of adhesive, acidity regulator, deionized water, etc. were mixed to prepare a coating slurry, and the alumina slurry was coated on a ceramic honeycomb carrier in an amount such that the honeycomb carrier contained 100 g / L of alumina. The coated honeycomb carrier was dried at 110° C. for 4 hours to obtain a cerium-zirconium composite oxide Ce. 0.30 Zr 0.61 La 0.044 Gd 0.04 Cu 0.006 Take 200g of O2 and add Ce 0.30 Zr 0.61 La 0.044 Gd 0.04 Cu 0.006 O2 and a certain amount of adhesive, acidity regulator, deionized water, etc. are made into a coating slurry, and Ce 0.30 Zr 0.61 La 0.044 Gd 0.04 Cu 0.006A slurry containing O2 was applied to the honeycomb carrier coated with Pt / Al2O3 at a coating amount of 100g / L, the coated honeycomb carrier was dried at 110°C for 4 hours, the honeycomb carrier was further heat-treated at 530°C for 7 hours, and finally the honeycomb carrier was roasted at 640°C for 5 hours to obtain a honeycomb-type precious metal catalyst, in which the precious metal Pt was mainly supported on the grain boundaries and surface of the Pt / Al2O3 of the honeycomb-type precious metal catalyst, and a small amount was supported on the grain boundaries and surface of the cerium-zirconium composite oxide and alumina. A catalytic performance test was performed on the sample, and the sample manufacturing steps and catalyst test conditions were the same as those of Comparative Example 2. The test results showed that the ignition temperature of CO was 293°C, the ignition temperature of NO was 288°C, and the ignition temperature of HC was 287°C.
[0090] (Example 46) Cerium-zirconium oxide (Ce) 0.3 Zr 0.6 La 0.05 Pr 0.05 Take 200g each of O2 and activated alumina, add a certain amount of deionized water and mix uniformly. Add a certain amount of palladium, platinum and rhodium nitrates to the slurry so that the honeycomb carrier active coating contains palladium 0.45%, platinum 0.13% and rhodium 0.01% in loading amount. Add a certain amount of adhesive, acidity regulator, deionized water, etc. to prepare coating slurry. Then, the slurry is coated on a ceramic honeycomb carrier with a total loading amount of 1.18g / L of honeycomb catalyst precious metals. The coated honeycomb carrier is dried at 110℃ for 4 hours, further heat-treated at 650℃ for 4 hours, and finally reduced and roasted at 550℃ for 6 hours in a hydrogen atmosphere to obtain a honeycomb-type precious metal catalyst. The precious metals Pd, Pt and Rh are supported on the grain boundaries and surfaces of the cerium-zirconium composite oxide and alumina of the honeycomb-type precious metal catalyst. A catalytic performance test was conducted on the sample. The sample preparation steps and catalytic test conditions were the same as those in Comparative Example 2. The test results showed that the ignition temperature of CO was 281°C, the ignition temperature of NO was 294°C, and the ignition temperature of HC was 287°C.
[0091] From the above Comparative Examples and Examples, by adopting the manufacturing method of the catalyst with precious metals supported on the grain boundaries and the surface and the honeycomb-type precious metal catalyst provided in the Examples of the present invention, and by controlling the atmosphere, temperature and time of the heat treatment and roasting steps, the obtained catalyst with precious metals supported on the grain boundaries and the surface and the honeycomb-type precious metal catalyst were found to emit no CO, NO, or other harmful substances after aging at 1000°C for 4 hours. X , and the ignition temperature for HC are all significantly lower than those of the catalyst prepared by the conventional method of the comparative example, and it can be seen that the catalyst has good high-temperature stability and catalytic activity. The embodiment of the present invention diffuses the precious metal into the grain boundaries and surfaces of the active coating containing cerium zirconium composite oxide or cerium zirconium composite oxide and alumina, thereby preventing the migration, aggregation and growth of the precious metal particles, thereby maintaining good catalytic activity of the precious metal catalyst, improving high-temperature stability, and reducing the amount of precious metal used.
[0092] As described above, the present invention relates to a catalyst carrying a precious metal on the grain boundaries and surface, a honeycomb-type precious metal catalyst, and its manufacturing method and use. The precious metal is dispersed on the grain boundaries and surface of alumina and / or a cerium-zirconium composite oxide. In the present invention, by carrying and dispersing the precious metal on the grain boundaries and surface of the catalyst, the grain boundaries and surface have abundant defect sites, which can improve the activity of the precious metal, and also realize the anchoring effect of the precious metal, preventing the migration, aggregation and growth of precious metal particles, maintaining the catalytic activity and high-temperature stability of the precious metal catalyst, and reducing the amount of precious metal used.
[0093] It should be understood that the above-mentioned specific embodiments of the present invention are only used to exemplarily explain or interpret the principles of the present invention, and are not intended to limit the present invention. Therefore, any modifications, equivalent replacements, improvements, etc. made without departing from the spirit and scope of the present invention shall be included in the scope of protection of the present invention. Furthermore, the appended claims of the present invention are intended to cover all changes and modifications that fall within the scope and boundaries of the appended claims, or the equivalent forms of such scope and boundaries.
Claims
1. A catalyst having a precious metal supported on the grain boundaries and surface, the catalyst comprising a precious metal G, alumina and / or a cerium zirconium composite oxide, the precious metal G being dispersed on the grain boundaries and surface of the alumina and / or cerium zirconium composite oxide, the general chemical formula of the cerium zirconium composite oxide being: Ce x Zr y M z O 2-α D δ where: M is a cationic doping element and D is an anionic doping element; 0≦x≦1, 0≦y≦1, 0≦z<0.5, and x, y, and z satisfy x+y+z=1; A catalyst having a precious metal supported on the grain boundaries and surface, characterized in that 0≦α≦0.1 and 0≦δ≦0.
1.
2. A honeycomb-type precious metal catalyst, the catalyst comprising a honeycomb carrier, a precious metal G and an active coating, the active coating being alumina and / or a cerium-zirconium composite oxide Ce. x Zr y M z O 2-α D δ said precious metal G being dispersed at the grain boundaries and surface of the active coating, wherein M is a cationic doping element and D is an anionic doping element; 0≦x≦1, 0≦y≦1, 0≦z<0.5, and x, y, and z satisfy x+y+z=1; A honeycomb-type precious metal catalyst, characterized in that 0≦α≦0.1 and 0≦δ≦0.
1.
3. 3. The catalyst according to claim 2, characterized in that the percentage of said cerium-zirconium composite oxide relative to the total mass of the active coating is between 0 and 100%, preferably between 30 and 70%.
4. Catalyst according to any one of claims 1 to 3, characterized in that the precious metal G at the grain boundaries and at the surface is in the metallic state or in the metallic and oxidized state.
5. 5. The catalyst according to any one of claims 1 to 4, characterized in that the precious metal G comprises one or a combination of one or more of Pt, Pd, Rh, Ir, Os, Ru, Au and Ag, preferably one or a combination of one or more of Pt, Pd, Rh and Ru.
6. The doping element M includes one or more combinations of rare earth elements other than cerium, transition metal elements other than zirconium and rare earth elements, alkaline earth metal elements, and Al, Si, Ga, Sn, and Bi, and the rare earth elements other than cerium include La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Sc, and Y, and preferably La, Pr, Nd, Sm, Eu.
6. The catalyst according to any one of claims 1 to 5, characterized in that the transition metal elements include Ti, V, Mn, Fe, Co, Ni, Cu, Zn, Nb, Mo, Hf, Ta and W, preferably Ti, Mn, Fe, Co, Ni, Cu, Nb, Hf, W and Mo, and the alkaline earth metal elements include Be, Mg, Ca, Sr, Ba, preferably Mg, Sr, Ba.
7. 7. Catalyst according to any one of the preceding claims, characterized in that the doping element D comprises one or a combination of more than one of the anions N, F and P.
8. 3. The honeycomb carrier catalyst according to claim 2, wherein the material of the honeycomb carrier is a porous ceramic or a metal.
9. 2. The catalyst having a noble metal supported on the grain boundaries and surface according to claim 1, characterized in that the amount of the noble metal G supported in the catalyst is 0.01% to 3%, preferably 0.1% to 2%, in mass fraction.
10. 3. The honeycomb-supported catalyst according to claim 2, wherein the amount of the precious metal G supported in the catalyst is 0.01 to 2.8 g / L, preferably 0.1 to 2 g / L.
11. The catalyst according to any one of claims 1 to 10, characterized in that the cerium zirconium composite oxide in the catalyst contains a cerium zirconium composite oxide having an element gradient distribution and / or a cerium zirconium composite oxide having a core-shell structure.
12. A step S1 of uniformly mixing a cerium-zirconium composite oxide and / or activated alumina with a liquid salt of a precious metal G; Step S2, which performs one or two heat treatments on the product obtained in step S1; and step S3, in which the product obtained in step S2 is reduced and roasted once or twice in air or a reducing atmosphere to obtain a catalyst in which the precious metal is supported on the grain boundaries and on the surfaces of the cerium-zirconium composite oxide and / or activated alumina.
13. The honeycomb-type precious metal catalyst is coated with one or more coating materials in layers or regions, the coating materials including cerium zirconium composite oxide, alumina, cerium zirconium composite oxide having precious metals supported on grain boundaries and surfaces, alumina having precious metals supported on grain boundaries and surfaces, and a mixture of cerium zirconium composite oxide and alumina having precious metals supported on grain boundaries and surfaces, and the manufacturing step of the honeycomb-type precious metal catalyst includes: Step B1, wherein the one or more coating materials are mixed uniformly with an adhesive, an acidity regulator and water in one or more steps to prepare a coating slurry; Step B2 of applying the coating slurry obtained in step B1 to a honeycomb carrier in one or more steps, or applying the coating slurry to the honeycomb carrier in regions or layers, and drying the honeycomb carrier; The method for producing a honeycomb-type precious metal catalyst according to claim 2 to 8, 10 or 11, further comprising a step B3 of heat-treating and / or roasting the product obtained in step B2 in air or a reducing atmosphere to obtain a honeycomb-type precious metal catalyst.
14. The method for producing a honeycomb-type precious metal catalyst according to any one of claims 2 to 8, 10, 11 or 13, characterized in that a coating slurry is prepared by uniformly mixing cerium-zirconium composite oxide and / or alumina, a precious metal salt or a liquid salt of a precious metal, an acidity regulator, an adhesive and water in one or more steps, the obtained slurry is applied to a honeycomb carrier in one or more steps, or the obtained slurry is applied to a honeycomb carrier in regions or layers and dried, and the dried honeycomb carrier is heat-treated or / and reduced-roasted in a reducing atmosphere.
15. The method according to any one of claims 12 to 14, characterized in that the heat treatment temperature is 200-800 ° C, and the heat treatment time is 0.5-24 h, preferably the heat treatment temperature is 400-700 ° C, and preferably the heat treatment time is 1-12 h.
16. The method according to claims 12 to 14, characterized in that the roasting temperature is 400-700°C and the time is 0.5h-24h, preferably the roasting temperature is 450-600°C and the roasting time is 1h-12h.
17. The reducing atmosphere is CO and H 2 The method according to any one of claims 12 to 14, characterized in that it comprises one or more of the following:
18. 15. The method according to claim 12, 14, characterized in that the liquid salt of the precious metal G comprises one or a combination of one or more of the following molten salts or aqueous solutions of chlorides, nitrates and acetates.
19. Use of the catalyst according to any one of claims 1 to 12 in the fields of automobile exhaust gas purification, industrial organic exhaust gas treatment, natural gas catalytic combustion, petrochemistry, hydrogen energy and batteries.
Citation Information
Patent Citations
Method for preparing palladium catalyst carried by composite oxides of Ce-Zr
CN1695799A
Combustion catalyst for gas turbine
JP1984062344A
Dispersed noble metal-containing alumina particle, its preparation process and exhaust gas purification catalyst
JP2002066335A